2005
DOI: 10.4161/cbt.4.7.1826
|View full text |Cite
|
Sign up to set email alerts
|

Chronic imatinib mesylate exposure leads to reduced intracellular drug accumulation by induction of the ABCG2 (BCRP) and ABCB1 (MDR1) drug transport pumps

Abstract: Imatinib mesylate is a selective tyrosine kinase inhibitor that is successfully used in the treatment of Philadelphia-positive chronic and acute leukaemia's, and gastrointestinal stromal tumors. We investigated whether the intended chronic oral administration of imatinib might lead to the induction of the intestinal ABC transport proteins ABCB1, ABCC1 (MRP1), ABCC2 (MRP2) and ABCG2. Using Caco2 cells as an in vitro model for intestinal drug transport, we found that continuous exposure (up to 100 days) with ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(140 citation statements)
references
References 0 publications
7
128
0
5
Order By: Relevance
“…2A). These membrane drug transporters are known to decrease the IUR of imatinib by active outwarddirected transport (Burger et al, , 2005. Zosuquidar is a selective inhibitor of P-glycoprotein (ABCB1), and elacridar is known to potently inhibit both P-glycoprotein and ABCG2 (Bihorel et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2A). These membrane drug transporters are known to decrease the IUR of imatinib by active outwarddirected transport (Burger et al, , 2005. Zosuquidar is a selective inhibitor of P-glycoprotein (ABCB1), and elacridar is known to potently inhibit both P-glycoprotein and ABCG2 (Bihorel et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Both influx and efflux transporters have been implicated in the active transport of imatinib into and out of cells (Eechoute et al, 2011). We have previously demonstrated that imatinib is a substrate of ABCB1 and ABCG2, which are efflux transporters modulating gastrointestinal absorption, distribution, and hepatic elimination of imatinib Burger et al, , 2005. These efflux transporters are also expressed at the blood-brain barrier, where they inhibit the disposition of imatinib in the brain (Oostendorp et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Since all discussed TKIs are orally active compounds, BCRP might limit their activity not only by mediating extrusion and inducing resistance in the tumour cells, but also by reducing their oral bioavailability. Using Caco-2 cells as an in vitro model for intestinal drug transport, Burger et al (2005) found that continuous exposure to imatinib upregulates the expression of BCRP and P-gp, which resulted in a decreased intracellular accumulation of imatinib. We have also recently shown that BCRP expression in Caco-2 cells is upregulated under folate-deficient conditions (Lemos et al, 2006b).…”
Section: Bcrp and Tki Bioavailabilitymentioning
confidence: 99%
“…[12][13][14] BCRP also belongs to the ABC efflux transporter superfamily 26 and is widely expressed in the small intestine, liver and placenta, influencing the absorption and disposition of a variety of substrates. 27,28 It is noteworthy that Petain et al reported that IM clearance in patients carrying the ABCG2 421C/A genotype was significantly lower than in those with the 421C/C genotype.…”
Section: Introductionmentioning
confidence: 99%